THE INFLUENCE OF APPLIED THEATRE ON THE DEVELOPMENT OF THE AUDIENCE (Journal of Contemporary Philology, 2021)
The main purpose of the paper is to point out the importance of applied theater that is performed outside the classical relation of stage performance in front of the audience in a classical theater. The role of applied theater is much more complex and aimed at strengthening the critical thinking and self-confidence of marginalized social groups in the community, developing creative processes in education by including drama in the education of primary and secondary school students. The paper points out the functionality and value of all the techniques used by the applied theater to influence the formation of a new theatrical audience through animation activities. The basic hypothesis in this paper is to prove that the forms of applied theater influence the development of the cultural needs of the audience, as well as that by getting acquainted with the forms of applied theater, the audience develops a deeply positive attitude towards theater. The paper will use an interdisciplinary theoretical method, which implies the use of the following theories: the theory of applied theater by Patrick Pavis, Jakob Levi Moreno, Augusto Boal; theories for the audience and the reception of works of art by Victoria de Aleksander, Darko Lukić, Maja Ristić, and Predrag Ognjenović. The outcome of the entire research should provide theoretical, but also a practical insight into the possibilities offered by the applied theater for the development of the audience in the theater.
Keywords: аpplied theater; audience animation; open theater forms; creativity; audience; art reception